2012
DOI: 10.4314/njp.v39i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Child sexual abuse in Zaria, Northwestern Nigeria

Abstract: Abstract:Background: Child sexual abuse has been reported from all corners of the globe, and all age groups and both sexes are affected. Although the trauma of abuse heals with time, it leaves long term psychological and medical problems. This study was aimed at documenting the pattern of child sexual abuse in Zaria, Northern Nigeria. Methods: Retrospective study of case notes of all patients seen with a history of sexual abuse, from August 2008 to October 2009, at a primary health centre in Northwestern Niger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
40
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(59 citation statements)
references
References 19 publications
(32 reference statements)
15
40
1
Order By: Relevance
“…All the CSA patients seen during the period under review were female and this agrees with other studies from the same region of Nigeria 13,14 but is in contrast with a study from the north of the country. 7 This might suggest that CSA involving boys in the south of Nigeria where this study was conducted is not considered a major public health problem or is not reported or seen as such. Also, since all the patients attended hospital with the complaint of penetrative sexual intercourse, it could be speculated that girls were more likely to be traumatized during sexual intercourse than boys, hence their preponderance.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…All the CSA patients seen during the period under review were female and this agrees with other studies from the same region of Nigeria 13,14 but is in contrast with a study from the north of the country. 7 This might suggest that CSA involving boys in the south of Nigeria where this study was conducted is not considered a major public health problem or is not reported or seen as such. Also, since all the patients attended hospital with the complaint of penetrative sexual intercourse, it could be speculated that girls were more likely to be traumatized during sexual intercourse than boys, hence their preponderance.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the preponderance of reports of female victims of CSA in Nigeria, [13][14][15] sexual assault involving boys is equally important and has been reported in the past. 7,12 The wide cultural and social acceptance of heterosexual behaviour in Nigeria 16,17 coupled with probable diagnostic insensitivity on the part of those caring for children might explain the wide gap in its reportage compared with female cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations